2007
DOI: 10.3390/12102270
|View full text |Cite
|
Sign up to set email alerts
|

A New Sesquiterpene Glycoside from the Aerial Parts of Saussurea triangulata

Abstract: Abstract:Column chromatographic separation of a MeOH extract of the aerial parts of Saussurea triangulata led to the isolation of a new sesquiterpene glycoside 6, together with three quinic acid derivatives, two phenolics, two sesquiterpene glycosides and two flavonoids. The new compound 6 was identified as amarantholidol A glycoside by spectroscopic and chemical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The known compounds were confirmed to be staphylionoside F ( 2 ), 8 dehydrovomifoliol ( 3 ), 9 icariside B1 ( 4 ), 10 6 S ,9 S ‐roseoside ( 5 ), 11 6 S ,9 R ‐roseoside ( 6 ), 11 amarantholidol A glycoside ( 7 ), 12 and calendin ( 2 ) 13 by comparison their physical data (1D NMR) with the previous reported (including CD) data.…”
Section: Resultsmentioning
confidence: 79%
“…The known compounds were confirmed to be staphylionoside F ( 2 ), 8 dehydrovomifoliol ( 3 ), 9 icariside B1 ( 4 ), 10 6 S ,9 S ‐roseoside ( 5 ), 11 6 S ,9 R ‐roseoside ( 6 ), 11 amarantholidol A glycoside ( 7 ), 12 and calendin ( 2 ) 13 by comparison their physical data (1D NMR) with the previous reported (including CD) data.…”
Section: Resultsmentioning
confidence: 79%
“…Yang et al reported the isolation of several sesquiterpene glycoside from the aerial parts of S. triangulata. [6]. However, the components responsible for the neuroprotective effects of S. triangulata still remain unidentified.…”
mentioning
confidence: 99%
“…Previous studies on this plant disclosed the presence of flavonoids, polyphenolic acids, and diterpenes [1 -6]. Our phytochemical investigation on the 50% EtOH extract of the title plant led to the isolation of 18 compounds, comprising clerodendranthuside B (1), a new 8b-hydroxyisopimarene-type diterpenoid glucoside, and clerodendranthuside C (2), a new rearranged abietanoid-type diterpenoid glucoside, along with sixteen known compounds including four lignans, i.e., syringaresinol [7], syringaresinol 4'-O-bglucopyranoside [8], 1-hydroxysyringaresinol [9], and 8-hydroxypinoresinol [10], five miscellaneous phenylpropanoids, i.e., 2,6,2',6'-tetramethoxy-4,4'-bis(2,3-epoxy-1-hydroxypropyl)biphenyl [11], albibrissinoside B [12], glypentoside C [13], ethyl caffeate [14], and (2S,E)-N-[2-hydroxy-2-(4-hydroxyphenyl)ethyl]ferulamide [15], two flavonoids, i.e., prunin [16] and (2S)-naringenin [17], one sesquiterpenoid glycoside, amarantholidol A glycoside [18], two triterpenoid glycosides, i.e., arjunglucoside I [19] and arjungenin-23,28-bis-O-glucopyranoside [20], one megastigmane, i.e., vomifoliol [21], and one anthraquinone, i.e., emodin [22]. Except for prunin, (2S)-naringenin, and vomifoliol, the above other compounds were reported from this genus for the first time.…”
mentioning
confidence: 99%